Moral Progress in the Public Safety Net: Access for Transgender and LGB Patients - Davis, Stephan (The Hastings Center report, 2014)
As a population, people who self-identify as lesbian, gay, bisexual, or transgender face significant risks to health and difficulty in obtaining medical and behavioral health care, relative to the general public. These issues are especially challenging in safety-net health care institutions, which serve a range of vulnerable populations with limited access, limited options, and significant health disparities. Safety-net hospitals, particularly public hospitals with fewer resources than academic medical centers and other nonprofit hospitals that also serve as safety nets, are under immense financial pressures. However, with the introduction in 2011 of standards for LGBT inclusion by The Joint Commission, showing progress on LGBT health care has become a compliance issue for hospitals. And because the health care community itself has contributed to LGBT health disparities through prejudice, disrespect, or inadequate knowledge that have made it difficult for LGB and especially T people to seek care or to obtain the care they need, there is a moral case for allocating scarce resources to this population: we owe them some investment in righting wrongs that the health care system itself has produced. So, where to begin in the typical safety-net hospital or clinic? Beyond staff training, which is essential and for which good models now exist, what does justice demand from a service-utilization perspective? Given the range of health care services that an LGBT person in the safety net may need or want, how should we set priorities? And what can't we promise to do for this member of our community?